Evolution of low weight at born in the state of Alagoas between 1998 to 2018 (Research, Society and Development, 2022)
Objective: Estimating the trend in birth weight and its relationship with determining factors in the state of Alagoas, Brazil. Methods: This is an ecological time series study whose sample was composed of live births in the State of Alagoas from 1998 to 2018. The source was the Information System on Live Births. Data regarding birth weight, maternal sociodemographic characteristics, and pregnancy-related characteristics were collected from the Department of Informatics of the Unified Health System Data. In the data analysis, the linear polynomial regression method was used and a significance level of 5% was adopted. Results: 1,199,161 live births were analyzed. 85,375 (7.1%) were low birth weight (LBW). The highest rate of BPN occurred in 2013 (7.6%). Live births of mothers aged ≥35 years showed an increasing and significant trend of BPN with an annual mean increase of 13.4% of births with LBW (p